Indices of adiposity as predictors of cardiometabolic risk and inflammation in young adults. Issue 1 (10th February 2015) - Pourshahidi, L. K.; Wallace, J. M. W.; Mulhern, M. S.; Horigan, G.; Strain, J. J.; McSorley, E. M.; Magee, P. J.; Bonham, M. P.; Livingstone, M. B. E.
Abstract: Background: Studies investigating obesity and cardiometabolic risk have focused on 'at‐risk' populations and methodological inconsistencies have produced equivocal findings. The present cross‐sectional study investigated indices of body composition as predictors of cardiometabolic risk and their relationship with inflammation in apparently healthy young adults. Methods: A fasting blood sample was taken from consenting adults (160 males, 32 females, aged 18–40 years) for assessment of cardiometabolic risk markers (blood pressure, lipid profiles and insulin resistance) and inflammatory markers (C‐reactive protein, tumour necrosis factor‐α, interleukin‐6, interleukin‐10 and adiponectin). Together with anthropometry, fat mass (FM) and fat‐free mass (FFM) were determined by dual‐energy X‐ray absorptiometry. FM was expressed in absolute terms (kg), as well as relative to total body weight (%), height [FM index (FMI, kg m −2 )] and FFM (FM : FFM, %). Results: Although anthropometric indices were associated with most cardiometabolic risk markers, the strongest relationship was observed with FMI. Relative to having a low cardiometabolic risk (≤2 markers above clinically relevant cut‐offs), each kg m −2 increase in FMI, increased the likelihood of having an increased cardiometabolic risk by 29% (odds ratio = 1.29; 95% confidence interval = 1.12–1.49). Inflammatory markers were not associated with body composition or cardiometabolic risk. Conclusions: FMI was the strongest predictor of overall cardiometabolic risk but not inflammation per se . However, anthropometric indices, such as body mass index and waist‐to‐height ratio, remain valuable surrogate measures of adiposity in this group, particularly when risk markers are considered independently.